One new protocatechuic acid methyl ester and one enantiomeric pair of dihydroflavones isolated from Phymatopteris hastata. (June 2021) - Chen, Junping; Dai, Xiling; Jiang, Can; Fu, Yuxi; Jiang, Tianju; Tang, Liping; Wang, Linrui; Wang, Quanxi; Huang, Guozheng; Cao, Jianguo
Graphical abstract: Highlights: Fourteen natural compounds including two new compounds were isolated from P. hastata . All the compounds were investigated for α -glucosidase inhibitory activity in vitro . Compound 11 acts as a noncompetitive inhibitor to α -glucosidase. Abstract: A phytochemical investigation of Phymatopteris hastata led to the isolation of fourteen natural compounds, including a novel protocatechuic acid methyl ester, [protocatechuic acid methyl ester-4- O -(6′- O -protocatechuoyl)- β -d -glucopyranoside, 1 ], and one enantiomeric pair of new dihydroflavones (2a/2b ), together with twelve known compounds (3 ∼14 ). The structures of the new compounds were elucidated following a comprehensive analysis of spectroscopic data from HR-ESI-MS, 1D and 2D NMR, and optical rotatory dispersion (ORD), as well as acidic hydrolysis. Compounds 1, 2, 4, 7, 9, 10, 12, and 13 were isolated from P. hastata for the first time. All compounds isolated from P. hastata were investigated for their α-glucosidase inhibitory activity in vitro . Compound 11 showed a significant α -glucosidase inhibitory activity (IC50 value of 88 ± 3.6 μg/mL) and acted as a noncompetitive inhibitor.